Alternative Synthesis of MCM-41 Using Inexpensive Precursors for CO2 Capture - Aquino, Guillermo Daniel (2023)
We explore the use of industrial sources of silicon and surfactant for obtaining low-cost MCM-41 materials and evaluate their performance as CO2 adsorbents. All of them presented a high specific surface area with different structural characteristics and textural properties. Interestingly, the MCM-41 manufactured with the most economical reagents presented a SBET of 1602 m2.g-1. The template was removed by using thermal treatments in an air atmosphere or a washing process. Preservation of silanol groups proved to be more effective under washing or mild thermal treatment conditions with the advantage of their lower cost and environmental benefit. Surface reactivity against CO2 was enhanced by anchoring APTS to silanol groups through wet grafting. All ami-no-functionalized materials showed a performance as CO2 adsorbents comparable to those reported in the literature, reaching values close to 30 cm3.g-1 at 25 °C and 760 mmHg. Samples with a higher concentration of silanol groups showed better performance. Our studies indicate that adsorbed CO2 is retained at least up to 50°C, and the CO2 is chemisorbed on the silica modified with amine groups. The chemisorbed gas at very low pressures points to the potential use of these materials for CO2 storage.